2013
DOI: 10.1002/chem.201301871
|View full text |Cite
|
Sign up to set email alerts
|

Design of Glycosyltransferase Inhibitors: Pyridine as a Pyrophosphate Surrogate

Abstract: A series of ten glycosyltransferase inhibitors has been designed and synthesized by using pyridine as a pyrophosphate surrogate. The series was prepared by conjugation of carbohydrate, pyridine, and nucleoside building blocks by using a combination of glycosylation, the Staudinger-Vilarrasa amide-bond formation, and azide-alkyne click chemistry. The compounds were evaluated as inhibitors of five metal-dependent galactosyltransferases. Crystallographic analyses of three inhibitors complexed in the active site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 83 publications
2
36
0
Order By: Relevance
“…In this respect, glycomimetics with free hydroxyl groups have proved not to be good candidates, suggesting that H‐bonding interactions are not the key in this case. On the other hand, a triazole ring engages in some interactions in the case of compound 18 ( K i =231.9 μ m ), in agreement with the findings of Vidal and co‐workers . However, the best result was found for compound 14 ( K i =102.5 μ m ), with a value of the order of those reported in the literature .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In this respect, glycomimetics with free hydroxyl groups have proved not to be good candidates, suggesting that H‐bonding interactions are not the key in this case. On the other hand, a triazole ring engages in some interactions in the case of compound 18 ( K i =231.9 μ m ), in agreement with the findings of Vidal and co‐workers . However, the best result was found for compound 14 ( K i =102.5 μ m ), with a value of the order of those reported in the literature .…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, the interactions of the NHAc group of the glucosamine moiety with His498 and His920, present in the crystal structure and MD simulations, are lost in 18 , which forms H‐bonding interactions with Tyr841 and Lys842. In contrast to previous docking studies, but in agreement with the STD‐NMR experiments, no interactions were found for the triazole ring.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…55a (axial) was a potent inhibitor of b-1,4-GalT and a weak inhibitor of the other enzymes, while 55b was a weaker inhibitor. 155 …”
Section: Enzyme Inhibitionmentioning
confidence: 99%
“…Although uridyl-phosphates are successfully elaborated towards potent glycosyltransferase inhibitors, [30][31][32] in the long term, the aminesubstituted derivatives would be advantageous due to the positive charge, which would enhancec ell permeability relative to negatively charged analogues, as hasb een an inspiration in several inhibitor design strategies. [33][34][35][36][37] Encouraged by these initial inhibition results, the mureidomimetics trategy was expandedt oc reate 'dyad inhibitors' that would display two binding modules. Instead of the alanine that had principally been incorporated to increase rigidity,atargeted screen was performed to identify am oiety that could potentially bind in the carbohydrate-binding site of the UDP-sugar substrate, and therefore our attentionw as focusedo n mono-a nd bicyclic aromatic compounds that could engage in p-stacking interactions often identified in sugar-binding sites.…”
Section: Strategy 1: Mureidomimeticsmentioning
confidence: 99%